PENGARUH PENERAPAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KEMAMPUAN MENULIS ESAI SISWA KELAS XII IPA SMA NEGERI 8 KOTA JAMBI - Erlina Zahar; Zarina Zarina (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
This research is aimed at describing the effect of cooperative integrated reading and composition (CIRC) model towards students essay writing at class XII IPA SMA N 8 Kota Jambi. The method used in this research is quasi experiment. There are two classes used in this reseach; they are class XII IPA 7 consists of 43 students as control class and class XII IPA 5 consists of 43 students as experimental class. Requirement test which is used is normality and homogenity test. The result of normality and homogenity test is 0,69 and 0,067 higher than significance α = 0.005. It means that in normal and homogenity research, hypothesis test can be done. Hypothesis test is required by using t test formula. The result of the research shows that the value of tcount = 2,559 higher that the value of ttable= 1,6746. In significance α= 0.05, dk is 52. Thus, it can be concluded that the effect of the application of cooperative integrated reading and composition (CIRC) model has significant effect towards students achievement in writing essay at class XII IPA SMA N 8 Kota Jambi. The mean score of the experimental class is 81,22 which is higher than the mean score of control class which is 72,78.  Keywords : Essay writing, Cooperative Integrated Reading and Composition (CIRC)